Clinical Efficacy of Early Administration of Convalescent Plasma among COVID-19 Cases in Egypt - Asem, Noha; Massoud, Hossam Hosny; Serag, Ihab; Hassany, Mohamed; ElAssal, Gehan; Abdelbary, Akram; Mohsen, Marwa; Baki, Amin Abdel; Zaky, Samy; Amin, Wagdy; Kamal, Ehab; Ibrahem, Hamdy; et al. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The rapid worldwide spread of the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) or COVID-19 pandemic from its epicenter; Wuhan was first reported in December 2019. Egypt reported its first COVID-19 case on February 14, 2020. Thereafter, Egypt scaled-up preventive measures, with a partial lockdown starting on March 25. Several therapeutic agents along with convalescent plasma transfusion (CPT) are under investigation and data from CPTs have been receiving a lot of attention, after Emergency approvals from the Food and Drug Administration suggesting that it may provide a clinical effect in the treatment of SARS-COV-2. IMPORTANCE: Early and effective treatment of COVID-19 is vital for control of SARS-CoV-2 infection. METHODS: Designs: An interventional, single-arm, and non-randomized clinical trial conducted in Egypt from April 15 to July 21, 2020. Settings: This was a multi-center study conducted in three hospitals in Egypt. Participants: A total of 94 COVID-19 laboratory-confirmed patients using quantitative real-time polymerase chain reaction were enrolled in the study. Intervention: All patients were administered with two plasma units (each unit is 200 cc). The volume of donated plasma was 800 cc. Main Outcome and measures: Primary measure was the degree of clinical improvement among the COVID-19 patients who received CPT within 7 days. RESULTS: A total of 94 patients were enrolled who received CPT either within 7 days or after 7 days of hospitalization. 82 were severely ill and 12 were critically ill. The average age remained 58 years (±standard deviation 15.1 years). Male were 69% and 49% patients got cured while 51% died with case fatality rate 51%. Seventy-five percent deaths were above 45 years of age. The symptoms were dyspnea (55%), fever (52%), cough (46%), and loss of taste and smell (21%), and cyanosis (15%). The most common co-morbidities among the <40 years remained diabetes mellitus (21%) and asthma (14%). Among 40–60 years hypertension (56%), diabetes mellitus (39%) and among >60 years age group hypertension (57%), and chronic heart disease (24%) were reported. CPT within 7 days remained significant as compared with the CPT after 7 days with the number of days to cure (p=0.007) and ICU stay (p = 0.008) among severely ill cured cases. CONCLUSIONS: Among patients with COVID-19 and severe or critical illness, the use of CPT along with routine standard therapy resulted in a statistically significant improvement when administered within seven days of hospital admission. However, plasma transfusion, irrespective of days to transfusion may not help treat critically ill patients. The overall mean time to cure in severely ill patients was 15 days if CPT provided within 7 days with 65% cure rate. TRIAL REGISTRATION: Clinical Intervention identifier: MOHP_COVID-19_Ver1.1 registered April 2020.